Climate Emergency Declaration and How Countries Respond - Aditya Bagus Permana (International Journal of Social Sciences and Humanities, 2026)
Declarations of climate emergency have arisen as a worldwide reaction to the intensifying peril of climate change, signifying an increasing political and legal acknowledgment of the climate issue. Following the initial statement by the Darebin local government in Australia in 2016, several governments globally have enacted analogous declarations to underscore the imperative of climate action. This study investigates the responses of national and international legal systems to climate emergency declarations and evaluates the various strategies employed by states in combating climate change. This research use qualitative methods, including case study and comparative methodologies, to assess legal developments, climate litigation, and policy implementation in multiple nations. The results indicate that climate emergency declarations, while frequently symbolic, are progressively impacting judicial review, public accountability, and environmental governance. Significant climate litigation cases, including Urgenda Foundation v. State of the Netherlands, Juliana v. United States, and Leghari v. Federation of Pakistan, exemplify the increasing influence of courts in pressuring governments and corporations to meet climate responsibilities. Moreover, international legal frameworks like the Paris Agreement and the UNFCCC establish significant normative bases for national climate policies. The study indicates notable disparities in state responses, with wealthy nations typically exhibiting superior institutional and financial capabilities for executing climate policy, whereas poor nations often encounter political, economic, and infrastructural constraints. Ultimately, climate emergency declarations serve as both political statements and mechanisms that can promote enhanced legal accountability, policy reform, and international collaboration in addressing the global climate problem.